Efficient and Layer‐Dependent Exciton Pumping across Atomically Thin Organic–Inorganic Type‐I Heterostructures. Issue 40 (30th August 2018) - Zhang, Linglong; Sharma, Ankur; Zhu, Yi; Zhang, Yuhan; Wang, Bowen; Dong, Miheng; Nguyen, Hieu T.; Wang, Zhu; Wen, Bo; Cao, Yujie; Liu, Boqing; Sun, Xueqian; et al.
Abstract: The fundamental light–matter interactions in monolayer transition metal dichalcogenides might be significantly engineered by hybridization with their organic counterparts, enabling intriguing optoelectronic applications. Here, atomically thin organic–inorganic (O–I) heterostructures, comprising monolayer MoSe2 and mono‐/few‐layer single‐crystal pentacene samples, are fabricated. These heterostructures show type‐I band alignments, allowing efficient and layer‐dependent exciton pumping across the O–I interfaces. The interfacial exciton pumping has much higher efficiency (>86 times) than the photoexcitation process in MoSe2, although the pentacene layer has much lower optical absorption than MoSe2 . This highly enhanced pumping efficiency is attributed to the high quantum yield in pentacene and the ultrafast energy transfer between the O–I interface. Furthermore, those organic counterparts significantly modulate the bindings of charged excitons in monolayer MoSe2 via their precise dielectric environment engineering. The results open new avenues for exploring fundamental phenomena and novel optoelectronic applications using atomically thin O–I heterostructures. Abstract : Atomically thin and layer‐dependent (organic–inorganic) O–I heterostructures are fabricated, which comprise monolayer MoSe2 and 2D limit pentacene. The heterostructures are observed to be of type‐I band alignment, showing efficient and layer‐dependent exciton pumping. In addition, substrate‐related and pentacene‐layer‐dependent modulation of the trion binding energies in monolayer transition metal dichalcogenides is also demonstrated.